Coherent diffractive imaging of microtubules using an X-ray laser - Gisela Brändén (Nature Communications, 2019)
XFEL radiation is providing new opportunities for probing biological systems. Here the authors perform nanoscale x-ray imaging of microtubules with helical symmetry, by using imaging sorting and reconstruction techniques.